Atomically-thin Bi₂MoO₆ nanosheets with vacancy pairs for improved photocatalytic CO₂ reduction - Di, Jun (2021)
Exploring efficient strategies to increase CO₂ photoreduction performance is a key challenge in the energy conversion field. Herein, a cooperative role involving an ultrathin 2D structure and surface defects is employed to design defective Bi₂MoO₆ ultrathin nanosheets, to boost the CO₂ photoreduction activity under water with no sacrificial agent, co-catalyst or extra photosensitizer. Bi₂MoO₆ ultrathin nanosheets with surface “Bi—O″ vacancy pairs are grown via a template-directed strategy, as proved by STEM-ADF and positron annihilation spectroscopy. The engineered “Bi—O″ vacancy pairs tune the local atomic structure, electronic structure of Bi₂MoO₆ and serve as charge separation centers to boost the electron-hole separation. Meanwhile, the defective ultrathin structure favors the CO₂ adsorption, activation and CO desorption processes. With the merits of atomically-thin configuration and surface defects, the defective Bi₂MoO₆ ultrathin nanosheets display 2.55 times improved CO formation rate than their bulk counterpart under light irradiation.